The Determinants of Fatal Outcomes during Severe Malaria in Children at the HKM University Teaching Hospital of Cotonou-Benin - SAGBO, GODONOU GRATIEN; ALIHONOU, FLORENCE NATHALIE YACOBA; ALAO, MODJÉRÉ OLA MAROUFOU JULES; TOHODJEDE, YEVEDO; ZOHOUN GUIDIBI, LUTECIA MYRIAME; BOGNON, GILLES (My University, 2017)
Introduction: Malaria particularly affects children in sub-Saharan African countries. This study aimed to investigate the factors associated with death in cases of severe childhood malaria to better understand the determinants of death in these children. Patients and Methods: This cohort, descriptive and analytical study was conducted from April 1 to August 15, 2015, at the CNHU-HKM pediatric clinic in Cotonou. Recruitment was exhaustive for all patients under 15 years of age who were admitted for severe malaria, as confirmed by thick smear microscopy. Results: Among the 1774 admitted patients, 449 had severe malaria caused by Plasmodium falciparum (i.e. , a hospital frequency of 25.31%). The age group most affected consisted of children younger than 60 months of age (73%); female predominance was noted. The lethality rate of malaria was 13.1% (n = 59). The factors associated with death were coma (p = 0.032), poor convulsive status epilepticus (p = 0.08) and bacterial co-infection by gram negative bacteria (p = 0.021) with respectively correlations coefficient of 0.003, 3.940 and 2.424. Conclusion: Reduction of the malaria mortality rates in Benin hospitals will depend on appropriate management of poor prognostic factors, such as coma, bacterial co-infection and convulsive illness.
Keywords: Children; Severe Malaria; Lethality; Neurological Disorders; Bacterial Infection